Does the cerebellar sequential theory explain spoken language impairments? A literature review. (3rd April 2021) - Lupo, M.; Olivito, G.; Angelini, L.; Funghi, G.; Pignatelli, F.; Siciliano, L.; Leggio, M.; Clausi, S.
ABSTRACT: During the past decades, converging evidence from clinical, neuroimaging and neuroanatomical studies has demonstrated the key role of the cerebellum in the processing of non-motor aspects of language. Although more is known about the way in which the cerebellum participates in the mechanisms involved in written language, there is ambiguous information on its role in other aspects of language, such as in non-motor aspects of spoken language. Thus, to contribute additional insight into this important issue, in the present work, we review several original scientific papers focusing on the most frequent non-motor spoken language impairments evidenced in patients affected by cerebellar pathology, namely, verbal working memory, grammar processing and verbal fluency impairments. Starting from the collected data, we provide a common interpretation of the spoken language disorders in cerebellar patients, suggesting that sequential processing could be the main mechanism by which the cerebellum participates in these abilities. Indeed, according to the cerebellar sequential theory, spoken language impairments could be due to altered cerebellar function to supervise, synchronize and coordinate the activity of different functional modules, affecting the correct optimization of linguistic processing.